Sustainable and responsible investment (SRI):trends and prospects - Syed Azman, Syed Marwan Mujahid; Engku Ali, Engku Rabiah Adawiah (Jabatan Kemajuan Islam Malaysia, 2016)
This paper focuses on highlighting the trends and prospects of Sustainable and Responsible Investment (SRI) financial instruments. It also explicates the potential role of SRI in propelling Malaysia further as the leader in the global Islamic finance industry. Based on review of literature and data from various sources, this paper finds that the growth of the Islamic finance industry has slowed down, correlating with the global economic and finance environment. However, the trend may improve, encouraged by the global interest in Socially Responsible Investment (SRI). The emergence of innovative SRI instruments such as Green bonds, vaccine sukuk, Social Impact Bond (SIB), and SRI sukuk is encouraging, especially for the growth of the Islamic finance industry. The paper compares SIB and SRI sukuk, and discusses the potential of SRI sukuk which can provide a huge opportunity for Islamic finance. The global SRI industry is still nascent but there is a growing demand and potential. Therefore, the issuances of SRI sukuk can potentially tap into this market and reinforce the universality of the value proposition of the Islamic finance industry. The paper contributes to the awareness of the SRI industry as well as the potential growth-path of the Islamic finance industry and the social impact it can bring.